"Maybe One Day I Will also be Almito": Ethiopian Israelis, Naming, and the Politics of Immigrant Identity. Issue 3 (September 2021) - Walsh, Sophie D; Yakhnich, Liat
The issue of name change, and in particular name reclaiming (i.e., taking back a heritage name), among immigrants has been rarely studied academically, despite its centrality to immigrant identity and immigration experiences. Immigrants, in many countries, are often encouraged or pressured to change their names, but in recent years, some have chosen to reclaim their heritage or original names. This article analyzes the practice of name reclaiming among young Israelis of Ethiopian heritage, a community that has experienced racial discrimination. Data were gathered through a qualitative phenomenological study of 19 young adults who immigrated to Israel from Ethiopia as minors. The analysis yielded two simultaneous dialogues: an internal dialogue in which individuals described their personal experience of name reclaiming and an external dialogue in which name reclaiming reflected a political and social process through which a discriminated minority could express increased feelings of power and agency. The results enrich the study of migration by showing the ways in which personal and social-political processes experienced by a discriminated minority intertwine, as vividly illustrated by the specific case of name reclaiming.